2020
DOI: 10.1016/j.btre.2020.e00512
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of physico-chemical properties and antioxidant activity of oil from seed, leaf and stem of purslane (Portulaca oleracea L.)

Abstract: Highlights Purslane is a portulacaceae family and is a very good source of alpha-linoleic acid. Alpha-linoleic acid is omega-3 fatty acid that plays a vital role in preventing diseases. Analysis of antioxidant activity of purslane oil and appraisal of its viability is very crucial. Physicochemical determination of oil from purslane revealed the highest oil content in seed. Illustrating chemical properties of purslane i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A chemical characterization and in vivo toxicological safety evaluation of emu oil was carried out in this study. The unesterified fatty acid levels of oil samples were assessed by the acid number and the contents of free fatty acids, thus defining their quality [ 31 ]. Here, emu oil possessed a low acid value and peroxide value.…”
Section: Discussionmentioning
confidence: 99%
“…A chemical characterization and in vivo toxicological safety evaluation of emu oil was carried out in this study. The unesterified fatty acid levels of oil samples were assessed by the acid number and the contents of free fatty acids, thus defining their quality [ 31 ]. Here, emu oil possessed a low acid value and peroxide value.…”
Section: Discussionmentioning
confidence: 99%
“…The garlic bulb and leek leaf samples were manually washed with distilled water and residual moisture evaporated at room temperature. Determination of moisture (on dry basis) was carried out [ 12 ]. The oil extraction was done in the Soxhlet apparatus using hexane as a solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The dry weights of the samples (leaves, flowers, and stems) from two different locations were investigated for potential antioxidant activity by Silva and Carvalho [ 41 ], who found that stems had a higher total phenolic content and total antioxidant activity than the flowers and leaves. The oil from seeds, leaves, and stems of P. oleracea were analyzed and found that the peroxide value was significantly higher for seed oil and the lowest for stem oil [ 51 ]. Furthermore, the highest ascorbic acid content was found for P. oleracea seed oil (41.67%), followed by leaf oil (32.29%), and the highest DPPH was obtained for leaf oil (12.55%), followed by seed oil (2.05%).…”
Section: Potential Antioxidant Of the P Oleraceamentioning
confidence: 99%